Iodine status in premature newborns - Ibrahim, Rana; Krylová, Kateřina; Neumann, David (Casopis lekaru ceskych, 2021)
Iodine is a micronutrient essential for normal thyroid function, growth and development of a child. Iodine deficiency remains an unresolved problem worldwide, where even in countries with adequate iodine supply certain population groups remain particularly at risk. Premature newborns comprise one such group as several factors including organic and functional developmental immaturity, a lower iodine reserve pool and insufficient postnatal iodine intake may contribute to iodine deficiency. However, such newborns are also more susceptible to autoregulatory thyroid inhibition upon excessive iodine supply. Several guidelines on the optimal daily iodine intake for preterm newborns exist in different parts of the world. Our article presents an overview of these guidelines and current data about iodine content in parenteral nutrition, breast milk and milk formulas.
Keywords: Parenteral Nutrition; novorozenec; Infant, Newborn; Humans; thyroid gland; dítě; Child; jod; parenterální výživa; Female; urinary iodine concentration; lidé; Iodine; Pregnancy Complications; Thyroid; iodine; premature newborn; ženské pohlaví; komplikace těhotenství